2015
DOI: 10.1111/cpf.12302
|View full text |Cite
|
Sign up to set email alerts
|

Measuring breathing patterns and respiratory movements with the respiratory movement measuring instrument

Abstract: The RMMI can be used to measure and analyse different breathing patterns in different body positions, and the correlation between measured RMs and breathing volumes is strong.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
18
1
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(22 citation statements)
references
References 30 publications
1
18
1
2
Order By: Relevance
“…The ability for thorax expansion and the respiratory muscle strength correlated (moderately) with the pulmonary function (TLC, FVC, and FEV 1 ), whereas the breathing movements (RMMI) did not show any correlations of significance. Hagman et al [38] found a strong correlation between measured breathing movements and breathing volumes. They did their measurements, with RMMI and a dynamic spirometer, simultaneously in three different body positions-supine, sitting on a chair, and standing with the back against a wall.…”
Section: Correlations Between Resultsmentioning
confidence: 96%
“…The ability for thorax expansion and the respiratory muscle strength correlated (moderately) with the pulmonary function (TLC, FVC, and FEV 1 ), whereas the breathing movements (RMMI) did not show any correlations of significance. Hagman et al [38] found a strong correlation between measured breathing movements and breathing volumes. They did their measurements, with RMMI and a dynamic spirometer, simultaneously in three different body positions-supine, sitting on a chair, and standing with the back against a wall.…”
Section: Correlations Between Resultsmentioning
confidence: 96%
“…2,15,[34][35][36][37] Two studies reported the population source and participant selection, 2,36 whereas we were unable to determine this information in 4 studies 15,34,35,37 Five studies did not report a power analysis. 2,15,34,35,37 Furthermore, 2 studies did not present the actual P values. 34,37 One study did not describe the distribution of confounding factors.…”
Section: Methodological Quality Of the Studiesmentioning
confidence: 89%
“…The total score of individual studies was between 6 and 14. Five studies indicated high quality, 2,[34][35][36][37] whereas one study showed low quality 15 (Table 1). No studies reported on allocation concealment.…”
Section: Methodological Quality Of the Studiesmentioning
confidence: 99%
“…В последние полтора-два десятилетия исследованиям по восстановлению сердечного ритма (ВСР) после физических нагрузок придается важное значение как в медицине, так и при организации физического воспитания и спорта. Рядом исследователей [1,2] установлено, что замедленное восстановление частоты пульса является предиктором смертности у пациентов с риском кардиологических заболеваний. У детей и подростков индикаторы ВСР имеют отрицательную связь с показателями сердечно-сосудистого риска [3,4] и избыточной массой тела [4], используются как предикторы состояния здоровья и качества жизни после операций по пересадке сердца [5,6].…”
Section: Introductionunclassified
“…Проводят расчеты показателей восстановления относительно частоты пульса, зарегистрированного в конце нагрузки (PS ex ). Определяют величину снижения частоты пульса (PS) [1,2] или отношение величины пульса, зарегистрированного в определенное время восстановительного периода, к PS ex (rPS ext ) [9,10]. Некоторые авторы [6,11] рекомендуют определять ВСР по углу наклона линейной регрессии частоты пульса ко времени восстановления в течение 1-й минуты после прекращения нагрузки.…”
Section: Introductionunclassified